Turn on thread page Beta
    • Thread Starter
    Offline

    17
    ReputationRep:
    x^4-3x^3+5x^2-3x+6=x(x-2)^2(x+1)+A(x-2)(x+1)+B(x+1)+C(x-2)^2

    I got B=4 , C=2

    when comparing coeff of x^2 to find A

    I get  5=-2+A+C

    Meaning A=5

    however the book has it down as A=3

    Am i wrong?
    • Community Assistant
    Offline

    20
    ReputationRep:
    Community Assistant
    (Original post by joyoustele)
    x^4-3x^3+5x^2-3x+6=x(x-2)^2(x+1)+A(x-2)(x+1)+B(x+1)+C(x-2)^2

    I got B=4 , C=2

    when comparing coeff of x^2 to find A

    I get  5=-2+A+C

    Meaning A=5

    however the book has it down as A=3

    Am i wrong?
    Yeah.

    Did the first one in my head but the coeff of x^2 should be 0, not -2, if I’m not mistaken. Check it
    Offline

    20
    ReputationRep:
    (Original post by joyoustele)
    x^4-3x^3+5x^2-3x+6=x(x-2)^2(x+1)+A(x-2)(x+1)+B(x+1)+C(x-2)^2

    I got B=4 , C=2

    when comparing coeff of x^2 to find A

    I get  5=-2+A+C

    Meaning A=5

    however the book has it down as A=3

    Am i wrong?
    yes you are wrong. if you let x = 0 , B = 4 & C = 2 then you get A = 3
    • Thread Starter
    Offline

    17
    ReputationRep:
    (Original post by the bear)
    yes you are wrong. if you let x = 0 , B = 4 & C = 2 then you get A = 3
    Yh, i should have tried this too.
    Offline

    20
    ReputationRep:
    (Original post by joyoustele)
    Yh, i should have tried this too.
    as a lazy person i would use x = 0 as it is less work :teehee:
    • Thread Starter
    Offline

    17
    ReputationRep:
    (Original post by RDKGames)
    Yeah.

    Did the first one in my head but the coeff of x^2 should be 0, not -2, if I’m not mistaken. Check it
    x(x-2)^2(x+1)

    x^2-4x+2(x+1)x

    x(x^3-3x^2-2x+2)

    x^4-3x^3-2x^2+2x

    Coeff of x^2 =-2 + coeff of C x^2

    I know its A=3 now, but i cant see where i went wrong here
    • Thread Starter
    Offline

    17
    ReputationRep:
    (Original post by the bear)
    as a lazy person i would use x = 0 as it is less work :teehee:
    Yh, I shall start doing that. Ty
    • Community Assistant
    Offline

    20
    ReputationRep:
    Community Assistant
    (Original post by joyoustele)
    x(x-2)^2(x+1)

    x^2-4x+2(x+1)x

    x(x^3-3x^2-2x+2)

    x^4-3x^3-2x^2+2x

    Coeff of x^2 =-2 + coeff of C x^2

    I know its A=3 now, but i cant see where i went wrong here
    Second line. Constant of the expanded quadraric is 4, not 2.
    • Thread Starter
    Offline

    17
    ReputationRep:
    (Original post by RDKGames)
    Second line. Constant of the expanded quadraric is 4, not 2.
    oh.:facepalm:

    -TY
 
 
 
Poll
Do you think parents should charge rent?
Useful resources

Make your revision easier

Maths

Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

Equations

How to use LaTex

Writing equations the easy way

Student revising

Study habits of A* students

Top tips from students who have already aced their exams

Study Planner

Create your own Study Planner

Never miss a deadline again

Polling station sign

Thinking about a maths degree?

Chat with other maths applicants

Can you help? Study help unanswered threads

Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Write a reply...
Reply
Hide
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.